2021
DOI: 10.1002/alz.12255
|View full text |Cite
|
Sign up to set email alerts
|

The chronic neuropsychiatric sequelae of COVID‐19: The need for a prospective study of viral impact on brain functioning

Abstract: Introduction:The increasing evidence of SARS-CoV-2 impact on the central nervous system (CNS) raises key questions on its impact for risk of later life cognitive decline, Alzheimer's disease (AD), and other dementia.Methods: The Alzheimer's Association and representatives from more than 30 countries-with technical guidance from the World Health Organization-have formed an international consortium to study the short-and long-term consequences of SARS-CoV-2 on the CNS-including the underlying biology that may co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
166
0
9

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(182 citation statements)
references
References 164 publications
(338 reference statements)
7
166
0
9
Order By: Relevance
“…The vertexwise visualisation on the cortical surface of this loss of grey matter in the insula spatially corresponds in particular to the area of consistent activation to all basic taste qualities 43 . Interestingly, early neurological signs in COVID-19 are hyposmia and hypogeusia, which appear to precede the onset of respiratory symptoms in the majority of affected patients 2,11,44 . In addition, a popular hypothesis has been that an entry point to the central nervous system is via the olfactory bulb 2,5 .…”
Section: Discussionmentioning
confidence: 99%
“…The vertexwise visualisation on the cortical surface of this loss of grey matter in the insula spatially corresponds in particular to the area of consistent activation to all basic taste qualities 43 . Interestingly, early neurological signs in COVID-19 are hyposmia and hypogeusia, which appear to precede the onset of respiratory symptoms in the majority of affected patients 2,11,44 . In addition, a popular hypothesis has been that an entry point to the central nervous system is via the olfactory bulb 2,5 .…”
Section: Discussionmentioning
confidence: 99%
“…The framework of the reasons for non-testing and possible measures to tackle them cal readiness of patients to receive a COVID-19 diagnosis, are important but seemingly neglected issues. 14 If almost 1 in 5 people diagnosed with COVID-19 are diagnosed with a mental illness within 3 months of their positive test, 15 with prevalent neuro-psychiatric sequelae, 16 then our perception and the importance of this infection must be reconsidered. This is further aggravated by the negative consequences of loneliness and isolation, in addition to the disease itself, 17,18 suggesting that this is a real public health priority at a population level.…”
Section: Isolation and Social Distancingmentioning
confidence: 99%
“…While some studies have shown that SARS-CoV-2 may directly infect the brain [19][20][21], potentially through the olfactory bulb [19], others have shown that SARS-CoV-2 is absent from the brain [22] and cerebrospinal fluid (CSF) [13]. COVID-19 has also been suggested to cause inflammation within the central nervous system (CNS) [18,22,23], as well as microvascular injury [22]. For example, the SARS-CoV-2 spike protein, which readily crosses the blood-brain barrier (BBB) [24,25], induces an inflammatory response within microvascular endothelial cells, leading to BBB dysfunction [25].…”
Section: Introductionmentioning
confidence: 99%